Jornalismo popular em Macapá: análise do programa radiofônico “Luiz Melo entrevista” - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2018)
The following article seeks to identify the approach and applications of the characteristics and fundaments of Popular Journalism in the state of Amapá through interviews of a radio program. It also analyses its characteristics, implications and consequences. That been given, the main goal is to understand how the Popular Communication in Macapá (Amapá) happens through one of the most enjoyed media channels, the radio. The radio program “Luiz Melo Entrevista” was used as the main object of study of this analysis. In order to reach our objectives we appealed to the Analysis of Content, having the Spiral of Silence and Folkcommunication theories as main guides. These two theories were essential to this study, given that the communication as the people’s expressions is examined here. Throughout this research we observed characteristc elements of pupular press in Amapá’s radio. Some of those elements are strengthened by characteristics exclusive to radio. However, we also notice that those characteristics not always fulfill their roles as a popular mean of communication or uphold the fundamental pillars of journalism.
Keywords: Jornalismo popular; Entrevista; Radiojornalismo; Rádio; CNPQ::CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::JORNALISMO E EDITORACAO